The RELATIONSHIP OF ARM LENGTH AND MUSCLE STRENGTH ARM WITH THE SERVICE ABILITY ON BATANG SAMO WOMEN’S VOLLEY BALL CLUB: HUBUNGAN ANTARA PANJANG LENGAN DAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN SERVIS ATAS PADA - Selby, Risfi; Manurizal, Lolia; Putra, Riwaldi (Journal Of Sport Education and Training, 2024)
This study aimed to determine the relationship between arm length and arm muscle strength with top serve ability at the village women’s volleyball club Samo village. This study used a correlation research model. This research carried out in Batang Samo village, Rambah district, Rokan Hulu regency. The population in this study were all players in women’s volleyball club of Batang Samo, totaling 16 people. The research instrument was the test and measurement: arm length measurement, arm muscle strength test, and test top serve ability. Data analysis used the person product moment correlation test and multiple regression correlation test. The research results showed that: (a) there was no significant relationship. Significant arm length with top serve ability at the village women’s volleyball club Samo stem with a value of rcalculate = 0.271 < rtable = 0.497, with a value of p = 0.293 > 0.05; (b) there was a significant relationship between arm muscle strength and top serve ability at the Batang Samo village women’s volleyball club with rcalculate = 0.714 < rtable = 0.497, with a value of p = 0002 > 0.05; and (c) there was a positive relationship significant arm length and arm muscle strength with the top serve ability in the Batang Samo village women’s volleyball club with a value of F Change + 0.009 <0.05, with Fcalculate = 6.965 > Ftable 3.74.